Informing the future : critical issues in health. (Institute of Medicine of the National Academies, 2003)
The Institute of Medicine: Adviser to the Nation -- Highlighted reports -- Global health and infectious disease -- Health sciences and the research enterprise -- Ensuring food safety and proper nutrition -- Assuring the public's health -- Health care delivery system and performance capabilities -- Human security and bioterrorism -- Military personnel and veterans -- Robert Wood Johnson Health Policy Fellowships Program -- Senior nurse scholar program -- Recent and upcoming reports.
Keywords: Health planning -- United States.; Public health -- United States.; Medical care -- United States.; Health planning.; Public health.; Health Planning; Public Health; Delivery of Health Care -- trends; Health Services Needs and Demand -- trends; Health Services Needs and Demands -- trends; United States; Santé publique -- Planification -- États-Unis.; Santé publique -- États-Unis.; Santé publique -- Planification.; Santé publique.; public health.; HEALTH & FITNESS -- Health Care Issues.; MEDICAL -- Public Health.; MEDICAL -- Health Policy.; HEALTH & FITNESS -- Diseases -- General.; MEDICAL -- Diseases.; MEDICAL -- Health Care Delivery.; Health planning; Medical care; Public health; Electronic texts.